건강한 성인에서의 알코올의 집단 약물동태/약물동력에 미치는 산소의 영향 연구 - 송병정; 백현문; 황시영; 채정우; 윤휘열; 권광일; Song, Byungjeong; Back, Hyun-moon; Hwang, Si-young; Chae, Jung-woo; Yun, Hwi-yeol; Kwon, Kwang-il (한국임상약학회지, 2017)
Objective: To develop a population pharmacokinetics (PK)/pharmacodynamics (PD) model for alcohol in healthy volunteers and to elucidate individual characteristics to affects alcohol's PK or PD including dissolved oxygen. Methods: Following multiple intakes of total 540 mL alcohol (19.42 v/v%) to healthy volunteer, blood alcohol concentration was measured using a Breathe alcohol analyser (Lion SD-400 $Alcolmeter^{(R)}$). A sequential population PK/PD modeling was performed using NONMEM (ver 7.3). Results: Eighteen healthy volunteer were included in the study. PK model of alcohol was well explained by one-compartment model with first-order absorption and Michaelis-Menten elimination kinetics. $K_a$, V/F, $V_{max}$, $K_m$ is $8.1hr^{-1}$, 73.7 L, 9.65 g/hr, 0.041 g/L, respectively. Covariate analysis revealed that gender significantly influenced $V_{max}$ (Male vs Female, 9.65 g/hr vs 7.38 g/hr). PD model of temporary systolic blood pressure decreasing effect of alcohol was explained by biophase model with inhibitory $E_{max}$ model. $K_{e0}$, $I_{max}$, $E_0$, $IC_{50}$ were $0.23hr^{-1}$, 44.9 mmHg, 138 mmHg, 0.693 g/L, respectively. Conclusion: Model evaluation results suggested that this PK/PD model was robust and has good precision.